Sikap atas Ikhtilaf Fiqh Ibadah menurut Yusuf al-Qaradhawi: Pencegahan Konflik Internal Umat Islam di Indonesia - Pasaribu, Ilhamsyah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
People today have access to the diverse opinions that exist within fiqh al-‘ibādah (jurisprudence of worship), which consequently leads to differences in religious practice. As a result, ikhtilāf (juridical disagreement) may arise, potentially giving way to conflict. How, then, should a Muslim respond to ikhtilāf within fiqh al-‘ibādah? Yusuf al-Qaradawi has proposed a particular attitude toward dealing with ikhtilāf in matters of worship. This study seeks to explore the attitude recommended by Yusuf al-Qaradawi in addressing ikhtilāf within fiqh al-‘ibādah. To answer this question, a doctrinal legal research method was employed. The primary data source is his work al-Ṣaḥwah al-Islāmiyyah bayna al-Ikhtilāf al-Mashrū‘ wa al-Tafarruq al-Madhmūm. The findings indicate that there are six recommended attitudes for dealing with ikhtilāf in fiqh al-‘ibādah to prevent conflict: first, sincerity toward Allah (SWT) and detachment from personal desires; second, avoidance of fanaticism (ta‘aṣṣub), whether toward a teacher, a school of thought, or a group; third, maintaining good assumptions about others; fourth, refraining from blaming or finding faults in fellow Muslims; fifth, avoiding argumentative behavior and obstinacy in disputes; and sixth, engaging in dialogue through the best and most respectful means.